The macroeconomic consequences of disasters - Ilan Noy (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
Natural disasters have a statistically observable adverse impact on the macro-economy in the short-run. Not surprisingly, costlier events cause more pronounced slowdowns in production. Yet, interestingly, developing countries, and smaller economies, face much larger output declines following a disaster of similar relative magnitude than do developed countries or bigger economies. A close study of the determinants of these adverse macroeconomic output costs reveals several interesting patterns. Countries with a higher literacy rate, better institutions, higher per capita income, higher degree of openness to trade, and higher levels of government spending are better able to withstand the initial disaster shock and prevent further spillovers into the macro-economy. These all suggest an increased ability to mobilize resources for reconstruction. Financial conditions also seem to be of importance; countries with more foreign exchange reserves, and higher levels of domestic credit, but with less-open capital accounts appear more robust and better able to endure natural disasters, with less adverse spillover into domestic production.
Keywords: O40; Q54; 330; natural disasters; growth; Naturkatastrophe; Makroökonomischer Einfluss; Schätzung; Welt